PENGARUH INTELLECTUAL CAPITAL DAN CAPITAL STRUCTURE TERHADAP FIRM PERFORMANCE PERUSAHAAN MANUFAKTUR - Su Lian Silvya, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research was to study the effect of Intellectual Capital (HCE, SCE, and CEE) and Capital Structure (DER) on Firm Performance of the manufacturing companies listed in the Indonesia Stock Exchange in the period of 2016-2018. In this research there are 69 selected manufacturing companies that were listed on the Indonesia Stock Exchange in the 2016-2018 period so that the required data were 207 data samples. In this research panel model trial and hypothesis test were conducted. The results of this study indicate that HCE partially has no influence on company’s Return on Assets (ROA), while SCE and CEE partially has a positive influence on the company's Return on Assets (ROA) and Debt to Equity Ratio partially has a negative influence on company’s Return on Assets (ROA).